Comparison of the radiochromic EBT2 responses for4 MV LINAC in calibration processes - Sabrina Donato Silva; André L.S Castro; Thais Melo Mendes; Luciana B. Nogueira; Tarcisio Passos Ribeiro Campos (Brazilian Journal of Radiation Sciences, 2019)
Actually, cancer has gained a larger dimension and become a global public health problem. Radiotherapy (RT) is a neoplasia treatment and RT linear accelerators must undergo a strict dose quality control. Water or solid water phantoms can be used with this intuit. In recent years, radiochromic films with equivalent tissue composition have been widely used as dosimeters in the medical field. In this work the proposal was to analyze two distinct radiochromic film responses in water and solid water phantoms, a LINAC spectrum of 4MV beam. Solid water phantom, water phantom and EBT2 Radiochromic films were set in two distinct process of calibration. Films were exposed to a set of absorbed doses established by distinct monitor units (MU) specified in RT-center. Mathematical relations between the degree of red-intensity from digitized films and the absorbed dose for both methods were established. The coefficients of the polynomial function of the calibration curve were determined from the Origin software. The uncertainty of both processes was analyzed. The efficiency of the two calibration processes was set up. The adjustment of the calibration curve provided the coefficients of the second-order equation that relates the dose absorbed with the optical density of the film. The uncertainty regarding the calibration performed in water and solid water and the dose-error accuracy are in agreement with the literature. Both water and solid water were effective in calibration and can be used in routines of quality-control measurements. The results show that EBT2-radiochromic films are suitable to for dose-calibration in RT.